Stearic Acid Functionalized Iron Nanoparticle Based Magnetic Solid-Phase Extraction (MSPE) for the Determination of Oxadiazon in Purslane by High-Performance Liquid Chromatography (HPLC) - Tekin, Zeynep; Ozdogan, Nizamettin; Karlidag, Nazime Ebrar; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2023)
An accurate, simple, and sensitive method was developed for the determination of the herbicide oxadiazon in purslane. The method was based on magnetic solid phase extraction (MSPE) using stearic acid modified iron oxide nanoparticles (Fe3O4@SA) as the adsorbent for preconcentration, followed by the reverse phase high performance liquid chromatography (HPLC) determination of oxadiazon. The MSPE method was optimized using the univariate approach of optimization, where one parameter was tested at different variables and the other parameters were held constant. Using the optimum conditions, the oxadiazon limits of detection and quantification (LOD and LOQ) were 0.29 and 1.0 ng mL(-1). The calibration plot of the method was linear across a broad dynamic range from 1.0 to 1000 ng mL(-1) with a coefficient of determination equal to 0.9988. The accuracy and applicability of the method was validated by performing spike recovery experiments with purslane samples. The matrix matching calibration strategy was used to mitigate interferences from the sample to attain recovery values between 90 and 110%. The high recoveries and low standard deviations (<10%) verified the accuracy and precision of the developed protocol.
Keywords: High-performance liquid chromatography (HPLC); iron oxide nanoparticles; magnetic solid-phase extraction (MSPE); oxadiazon; purslane; GAS-CHROMATOGRAPHY; QUECHERS EXTRACTION; ENVIRONMENTAL WATER; MICROEXTRACTION; PESTICIDES; SAMPLES; PRECONCENTRATION; FRUIT; SPECTROMETRY; COMBINATION; Chemistry